Physical and emotional sibling violence and policy: An examination of Fox-Harding's child care value perspectives. Issue 1 (2nd January 2017) - Perkins, Nathan H.; Coles, D. Crystal; O'Connor, Mary Katherine
ABSTRACT: Physical and emotional sibling violence has received minimal attention compared with other forms of familial violence. Policy related to addressing physical and emotional sibling violence is scant, whereas the occurrence of violence between siblings is rampant in many families. An overview of the knowledge base regarding this social problem is provided as a backdrop for understanding the current sociopolitical status of sibling violence. Understanding current policy and societal discourse related to addressing sibling violence is possible through Lorraine Fox-Harding's values perspective on childcare policy. The four value perspectives of laissez-faire and patriarchy, state paternalism and child protection, the modern defense of the birth family and parents' rights, and children's rights and child liberation allow insight into how sibling violence is currently viewed and the policy implications of those perspectives. Regardless of one's value perspective, actions around policy and family interventions for sibling violence is warranted. Alternatives to the current situation and consequences of not addressing violent behavior between siblings are discussed along with roles the government, parents, and children can take in addressing this oftentimes underrecognized social justice issue.